Efektivitas Pembelajaran Online di Pendidikan Tinggi pada Masa Covid-19 - windasari windasari; Muhammad Kharis Fajar (Universitas Muhammadiyah Surakarta, 2021)
Covid-19 has brought a transformation of the learning process in higher education, from conventional to online learning. Learning process in higher education is using online learning during the Covid-19 pandemic period. The purpose of this study is to analyze the effectiveness of implementation online learning and exploring student perceptions about online learning at Universitas Negeri Surabaya. The research method in this study used mix method, quantitative descriptive and qualitative. The research sample is active students in the faculty of sports science with totall 180 respondents. The sampling technique is cluster random sampling. Data analysis to answer the research problem use descriptive quantitative and qualitative primary data analysis. The results showed online learning in Higher Education during the Covid-19 period could not be fully effective. To carry out effective online learning, students expected responsive communication and feedback from the instructor or instructor.